2012
DOI: 10.1590/s0102-311x2012000900006
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdade social no adoecimento e morte por câncer de boca e orofaríngeo no município de São Paulo, Brasil: 1997 a 2008

Abstract: A ocupação do espaço geográfico é determinada historicamente pelo modelo socioeconômico e pelo dinamismo de suas relações sociais, políticas e ideológicas. O objetivo deste trabalho é avaliar a distribuição espacial e o efeito de indicadores socioeconômicos no adoecimento e morte por câncer de boca e orofaríngeo no Município de São Paulo, Brasil, no período de 1997 a 2008. Os dados foram coletados no Registro de Câncer de Base Populacional e no Programa de Aprimoramento das Informações de Mortalidade - PRO-AIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
5
0
6
Order By: Relevance
“…It was also observed, similar to the present study, that patients with low education and high immunoexpression for TNF-α showed a worse survival rate, in addition to greater staging and use of surgery associated with radiotherapy and chemotherapy as a treatment of choice (Krishnan et al, 2014). In previous studies, patients with stage III and IV tumours expressed more TNF-α; in the researchers' country, patients with advanced disease stage are patients with a low level of education (Ferreira et al, 2012;Dantas et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…It was also observed, similar to the present study, that patients with low education and high immunoexpression for TNF-α showed a worse survival rate, in addition to greater staging and use of surgery associated with radiotherapy and chemotherapy as a treatment of choice (Krishnan et al, 2014). In previous studies, patients with stage III and IV tumours expressed more TNF-α; in the researchers' country, patients with advanced disease stage are patients with a low level of education (Ferreira et al, 2012;Dantas et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that low social and economic status and deprivation are significantly associated with an increased risk of oral cancer [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Among the studies that involve questions related to associations between different geographical variables and spatial structure (33.3%), those which stand out are the methodological procedures with the LISA function, or local autocorrelation function (Galli;Neto, 2008;Paredes et al, 2010;Ferreira et al, 2012). Not many studies that involve more complex spatial questions about interaction and change were found; in these cases, the spatial prediction techniques stand out, such as Kriging (Camargo et al, 2008;Cruz, 2011).…”
Section: Resultsmentioning
confidence: 99%